ANALYSIS OF THE IMPLEMENTATION OF MODERN AND TRADITIONAL EDUCATION SYSTEMS: A CASE STUDY AT PONDOK PESANTREN NURUL BAYAN - Andrian Syahidu; Ayu Mardianti; Iramasan Efendi; Samsul Hadi (International Conference on Social and Islamic Studies, 2021)
The modern and traditional (salaf) education system is an education system implemented by several Islamic boarding schools (Pondok Pesantren) in Indonesia. This model boarding school uses classical books and modern scientific knowledge. In addition, Islamic boarding schools run formal and non-formal education. For this reason, this article will examine the application of the Modern and Salaf Education system in learning and what are the obstacles in the Nurul Bayan Islamic Boarding School. This study aims to determine the application of the modern education system and salaf in learning and what are the obstacles to the implementation of the modern and salaf education system at the Nurul Bayan Islamic Boarding School. This study is a qualitative research by prioritizing data about the education and teaching process at the Nurul Bayan Islamic Boarding School, therefore the data collection procedure was obtained through observation, interviews and observations. This study found that the Nurul Bayan Islamic Boarding School is included in the category of Modern Islamic Boarding School, which integrates two education systems, namely the modern education system and the Salaf. This can be seen from the activities designed through the existing curriculum at the institution.